Analiza taksonomiczna powiatów województwa śląskiego z uwzględnieniem rozwoju demograficznego i gospodarczego - Sojka, Elżbieta (Taxonomic Analysis of the Silesian Voivodship Administrative Districts in Terms of Demographic and Economic Development, 2009)
In the article, the taxonomic analysis of Silesian voivodship districts has been carried out in terms of level of demographic and economic development using aggregative indicator of development. The dynamics of calculated indicators between 2000 and 2006 has also been examined. The results show that there is no direct compliance between economic and demographic development of Silesian voivodship districts. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 477-484